How does media richness contribute to customer loyalty to mobile instant messaging?. Issue 3 (5th June 2017) - Tseng, Fan-Chen; Cheng, T.C.E.; Li, Kai; Teng, Ching-I
Abstract : Purpose: No studies in the extant literature have explored the role of media richness, i.e., the ability of media to enhance understanding among communication partners in a timely manner, in determining customer loyalty to mobile instant messaging (MIM). Grounded in media richness theory, the purpose of this paper is to examine how media richness influences customer perceived values, consequently contributing to customer loyalty to MIM. Design/methodology/approach: Collecting data by an online survey, the authors apply partial least square procedures for hypothesis testing. Findings: The authors obtain the following findings: multiple cues are positively related to functional value; immediate feedback is positively related to social value; personal focus is positively related to self-expressive value; language variety is positively related to all the above values that lead to user loyalty; and language variety has the strongest effect on user loyalty to MIM. Originality/value: A first attempt to examine the impact of media richness on user loyalty to MIM, this study provides insights for MIM service providers to make decisions to build loyal user bases.